Evaluation of the impact of self-employment factors on self-employment duration in the country with transition economy: a Lithuanian case - Startienė, Gražina; Remeikienė, Rita (Technological and Economic Development of Economy, 2013)
The focus of this article is the factors of self-employment duration having the bidirectional effect (positive or negative) on a self-employed person. The research of the impact of bidirectional self-employment factors on self-employment direction has been encouraged by several reasons. Firstly, the scientific literature lacks of the research to focus on the factors motivating self-employment sustainability. The more abilities a person has to sustain self-employment activity, the more benefits he brings to the country (GDP creation, increase of employment, taxes paid) and his personal environment (ensured material well-being, good psychological state, realized objectives). Secondly, realising the impact of self-employment factors on self-employment duration, the government of the country can start application of the targeted business regulation measures that can help to increase the employment rate in the country. Using the methods of expert evaluation and correlation analysis, the impact of the highlighted self-employment factors on self-employment duration in the country with transition economy (Lithuanian case) has been evaluated: self-employment development is positively influenced by financial and non-financial business promotion measures, decreasing gross domestic product (GDP), extraversion, low level of neuroticism, openness, younger people, education andmarital status defined by having older children; it is negatively influenced by inflexible labour market, high unemployment rate, high income taxes and the immigrants. The article highlights the specificity of the country with transition economy considering the fact that business environment conditions in such countries are more difficult than in industrial countries.